Intra-articular Contact Stress Distributions at the Ankle throughout Stance Phase – Patient-Specific Finite Element Analysis as a Metric of Degeneration Propensity - Anderson, Donald D. (2006)
A contact finite element (FE) formulation is introduced, amenable to patient-specific analysis of cumulative cartilage mechano-stimulus attributable to habitual functional activity. CT scans of individual human ankles are segmented to delineate bony margins. Each bone surface is projected outward to create a second surface, and the intervening volume is then meshed with continuum hexahedral elements. The tibia is positioned relative to the talus into a weight-bearing apposition. The articular members are first engaged under light preload, then plantar-/dorsi-flexion kinematics and resultant loadings are input for serial FE solutions at 13 instants of the stance phase of level walking gait. Cartilage stress histories are post-processed to recover distributions of cumulative stress-time mechano-stimulus, a metric of degeneration propensity. Consistency in computed contact stress exposures presented for seven intact ankles stood in contrast to the higher magnitude and more focal exposures in an incongruously reduced tibial plafond fracture. This analytical procedure provides patient-specific estimates of degeneration propensity due to various mechanical abnormalities, and it provides a platform from which the mechanical efficacy of alternative surgical interventions can be estimated.